PENDEKATAN LOCATION QUOTIENT (LQ) KOMODITAS UNGGULAN TANAMAN PANGAN, SAYURAN DAN BUAH-BUAHAN DI KABUPATEN ROTE NDAO PROVINSI NUSA TENGGARA TIMUR - Chris N. Namah; Melgiana S. Medah (Partner, 2018)
The agricultural sector plays a vital role in Indonesian economic growth. The role of the agricultural sector had contributed 14.42 percent to national GDP in the third quarter of 2016 (BPS, 2017). The average production of food crops in Rote Ndao Regency is lower than the average production of NTT Province so that production needs to be boosted. The low rate of food production is caused by various factors such as natural factors, human resource factors, limited capital of farmers, and inadequate infrastructure. The Rote Ndao District government needs to address and anticipates these factors. The limitations of agricultural land encourage the selection of superior commodities following the Agroecology Zone (ZAE). Thus, research on superior commodities has been carried out using the Location Quotient (LQ) analysis in Rote Ndao. The results of the analysis show that for primary sector food crops (LQ> 1) there are Rote Barat Daya, Lobalain, Rote Selatan, Pantai Baru, Rote Timur, LanduLeko, and Rote Barat sub-districts. For vegetable commodities, superior sectors (LQ> 1) are inRote Barat Daya, Rote Barat Laut, Lobalain, Rote Tengah, Rote Selatan, Pantai Baru, Rote Timur, LanduLeko, West Rote, and Ndao Nusa. For fruit commodities (LQ> 1) are in West Rote District, Lobalain District, South Rote District, East Rote District, LanduLeko District, and West Rote District.